1997
DOI: 10.1177/107424849700200207
|View full text |Cite
|
Sign up to set email alerts
|

Review : Restoring Sinus Rhythm in Patients with Atrial Flutter and Fibrillation: Pharmacologic or Electrical Cardioversion?

Abstract: Atrial fibrillation and atrial flutter, the most frequently encountered tachyarrhythmias requiring treatment, have become a major focus for clinical and basic research in recent years. Restoration and maintenance of sinus rhythmn, having been shown to improve exercise capacity, alleviate symptoms, and reduce the incidence of thromboembolic events, may be the optimal management strategy. Identification of the safest, most efficacious and cost-effective means of restoring sinus rhythm is necessary prior to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…[34][35][36] However, it has been shown that restoration of sinus rhythm by early cardioversion results in early alleviation of symptoms and may lower the incidence of thromboembolism, thus eliminating the need for long-term use of AV nodal blocking drugs and possibly allowing earlier discharge from the hospital. 37 The advantages of rate control are that it is generally safe, well tolerated, and inexpensive. Its drawbacks are that there may be incomplete symptom resolution, bradycardia, the need for lifelong anticoagulation, and cardiomyopathy if the rate is poorly controlled.…”
Section: Management Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…[34][35][36] However, it has been shown that restoration of sinus rhythm by early cardioversion results in early alleviation of symptoms and may lower the incidence of thromboembolism, thus eliminating the need for long-term use of AV nodal blocking drugs and possibly allowing earlier discharge from the hospital. 37 The advantages of rate control are that it is generally safe, well tolerated, and inexpensive. Its drawbacks are that there may be incomplete symptom resolution, bradycardia, the need for lifelong anticoagulation, and cardiomyopathy if the rate is poorly controlled.…”
Section: Management Strategiesmentioning
confidence: 99%
“…45 The rate of spontaneous cardioversion to sinus rhythm within the first 24 hours is 30% to 50%, depending upon the duration of AF, and can be raised to 70% to 80% by pharmacological cardioversion and to 80% to 90% by electrical cardioversion. 37,46,47 External direct current cardioversion is the most effective means of cardioverting AF to sinus rhythm. The risk of proarrhythmia during cardioversion is very low.…”
Section: Cardioversion Of Atrial Fibrillationmentioning
confidence: 99%
See 2 more Smart Citations
“…Early conversion to normal sinus rhythm [NSR] improves symptoms, prevents the detrimental effects of prolonged AF and avoids hospitalization. 3 Conversion of AF can be achieved pharmacologically or by electrical cardioversion. Electrical cardioversion is effective but requires sedation and a fasting state.…”
Section: Introductionmentioning
confidence: 99%